Establishing Company Direction: A Literature Review of Management Strategy - Robbani, Yahya Taqiuddin; Denashurya, Tiara Grhanesia; Novrianto, Benny; Saputra, Zikri; Samosir, Kariaman Justiman; Susila, Luh Ayu Nanamy Khrisnashanti Eva; Alfiansyah, Vidi; Halim, Abdul (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
This research examines the literature on key concepts that drive strategy analysis, formulation, and implementation based on values, vision, and mission as guiding principles for determining a company's direction. This article utilizes a systematic literature review method to consolidate the findings of various studies and scientific literature. The process involves accessing and analyzing literature through digital search engines using keywords related to management strategies. The research uncovers a shortage of scientific literature containing important theoretical concepts that strategists can use as a roadmap for analyzing, formulating, and implementing strategies. This review adds to the existing literature by employing a management strategy approach to determine the company's direction.